Penerapan Algoritma CAST-128 pada Proses Enkripsi dan Dekripsi Teks - Yessi Sriani Barus; Abdul Sani Sembiring (Yayasan Kita Menulis, 2020)
Encoding was first made using a classic algorithm. This algorithm builds its security on the confidentiality of the algorithm used. However, this algorithm is inefficient when used to communicate with many people because the algorithm is still very simple and still very easy to solve, so important information or data that you want to keep secret can be easily discovered by other people or people who are not responsible. CAST-128 is a cryptographic algorithm that is said to be similar to the DES algorithm which uses 16 rounds of feistel network as one of its strengths. Where in the process of encryption and decryption of text CAST-128 uses a 64-bit block length and key lengths of up to 128 bits. For information, the CAST-128 algorithm is referred to as one of the strong cryptographic algorithms against various types of cryptanalysis, including differential and linear attacks. With the application of the CAST-128 algorithm in the process of encrypting and decrypting text, it will be more difficult to decode text encoded by people who do not know the key so as to create more security than the encoded text. So when the text wants to be sent or transferred to the flashdisk will be more confidential.